Body mass index and associated physical activity levels in 7 - 10-year-old children in primary schools in Port Elizabeth - Baard, M (South African Journal of Sports Medicine, 2014)
Background. Declining levels of physical activity coupled with the rising incidence of childhood obesity in developing countries are of health concern. Current daily recommendations for preadolescent children are to accumulate 60 min of moderate physical activity per day. In South Africa, physical education forms part of the life skills curriculum, but children have limited school time to engage in physical activity. As many obesogenic behaviours are learnt in childhood and track into adulthood, physical activity should be promoted at a young age and should be a research priority. Objectives. To explore and determine the association between body mass index (BMI) and daily physical activity levels as expressed in metabolic equivalent of task (MET) in 7 - 10-year-old children in quintile-5 English-medium primary schools in Port Elizabeth. Methods. A quantitative, descriptive, one-way, cross-sectional design utilising random sampling was used. A once-off survey comprised anthropometric assessment of height and weight of 713 participants. Age- and gender-specific prevalence rates of overweight, obesity and underweight were calculated based on the International Obesity Task Force (IOTF) cut-off points. One-way analysis of variance (ANOVA) and χ2 tests were performed. A validated once-off interviewer-administered physical activity questionnaire was utilised to determine daily energy costs. Results. The BMI of the majority of children fell within the norm and was coupled with high levels of daily physical activity (average of 893 METs). No significant relationship was found for BMI and physical activity (p=0.8). Conclusion. Daily level of physical activity is not significantly related to BMI in urban children from an economically privileged setting